Role of immune‐inflamed phenotype in the prognosis of hypopharyngeal carcinoma following primary surgery. Issue 1 (12th October 2022) - Chen, Renhui; Cai, Qian; Lin, Peiliang; Liang, Faya; Han, Ping; Zhang, Long; Song, Pan; Zhang, Tingzhen; Huang, Xiaoming
Abstract: Background: The immune profile in primary resected hypopharyngeal squamous cell carcinoma (HPSCC) and its prognostic value remain to be defined. Methods: We enrolled 100 patients with HPSCC underwent primary surgical resection at our department. HPSCC samples were examined using immunohistochemistry for the expressions of CD8, Foxp3, CD163, CD66B, programmed death ligand‐1 (PD‐L1), and interferon (IFN)‐γ. The immune pattern of the tumor microenvironment (TME) was discriminated into inflamed and non‐inflamed tumors based on the presence or absence of parenchymal CD8 + T cells. Results: We found that 74% of HPSCC cases in our cohort were characterized by an immune‐inflamed TME. Immune‐inflamed patterns demonstrated an inferior survival with a significantly increased density of CD163 + tumor‐associated macrophages and Foxp3 + regulatory T cells. Additionally, the inflamed tumor showed increased expression of PD‐L1, without IFN‐γ upregulation. Conclusions: The immune‐inflamed pattern is the predominant preexisting immune phenotype in HPSCC and demonstrates immunosuppressive immune cell recruitment.